2011
DOI: 10.1136/hrt.2010.213462
|View full text |Cite
|
Sign up to set email alerts
|

Utility of cardiac biomarkers for the diagnosis of type V myocardial infarction after coronary artery bypass grafting: insights from serial cardiac MRI

Abstract: Biomarkers alone (TnI), at an appropriate threshold appear robust for the detection of type V MI, independently of supplementary evidence, as suggested by the ESC/ACCF/AHA/WHF criteria. Clinical trial registration information The study is listed on the Current Controlled Trials Registry: ISRCTN41388968. URL: http://www.controlled-trials.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 27 publications
1
37
0
1
Order By: Relevance
“…To help provide useful and more timely differential data, some workers have been looking at techniques to assess preoperative risk other than clinical outcomes such as per-operative injury to the left ventricular myocardium. This is hard to quantify and was the subject of a recent study from Oxford in which 40 patients underwent cardiac MR before and after CABG with serial assessment of troponin I (TnI) 39. TnI correlated closely with the mass of new cardiac MR necrosis (r=0.83, p<0.001), with sensitivity and specificity values of 75% and 87%, making it a robust means of diagnosing this type of MI.…”
Section: Should Bilateral Internal Mammary Artery Grafts Be Used For mentioning
confidence: 99%
“…To help provide useful and more timely differential data, some workers have been looking at techniques to assess preoperative risk other than clinical outcomes such as per-operative injury to the left ventricular myocardium. This is hard to quantify and was the subject of a recent study from Oxford in which 40 patients underwent cardiac MR before and after CABG with serial assessment of troponin I (TnI) 39. TnI correlated closely with the mass of new cardiac MR necrosis (r=0.83, p<0.001), with sensitivity and specificity values of 75% and 87%, making it a robust means of diagnosing this type of MI.…”
Section: Should Bilateral Internal Mammary Artery Grafts Be Used For mentioning
confidence: 99%
“…2,3 Several studies have found that isolated troponin rise after CABG, measured with contemporary assays, independently predicts adverse outcomes. [3][4][5][6][7] High-sensitivity troponin assays have recently been developed, 8 being more sensitive than contemporary assays at detecting lower troponin levels. 1,9 The properties and utility of these assay may be different after CABG, and…”
Section: Introductionmentioning
confidence: 99%
“…This can be the result of many factors, including contact of blood with the bypass circuit, myocardial ischemia during bypass, aortic cross clamping, and reperfusion injury [36][37][38][39] [46][47][48]. Identifying CABG-related infarction using conventional ECG and biochemical methods, however, can be difficult.…”
Section: Surgical Interventionsmentioning
confidence: 99%